Lipidomics Analysis Indicates Disturbed Hepatocellular Lipid Metabolism in Reynoutria multiflora-Induced Idiosyncratic Liver Injury - Wu, Xiaofang; Zhang, Yating; Qiu, Jiaqi; Xu, Ya; Zhang, Jing; Huang, Juan; Bai, Junqi; Huang, Zhihai; Qiu, Xiaohui; Xu, Wen (Frontiers in Pharmacology, 2020)
The root of Reynoutria multiflora (Thunb.) Moldenke (syn.: Polygonum multiflorum Thunb., HSW) is a distinguished herb that has been popularly used in traditional Chinese medicine (TCM). Evidences of its potential side effect on liver injury have accumulated and received much attention. The objective of this study was to profile the metabolic characteristics of lipids in injured liver of rats induced by HSW and to find out potential lipid biomarkers of toxic consequence. A lipopolysaccharide (LPS)-induced rats model of idiosyncratic drug-induced liver injury (IDILI) was constructed and evident liver injury caused by HSW was confirmed based on the combination of biochemical, morphological and functional tests. A lipidomics method was developed for the first time to investigate the alteration of lipid metabolism in HSW-induced IDILI rat liver by using ultra-high performance liquid chromatography/Q-exactive Orbitrap mass spectrometry coupled with multivariate analysis. A total of 202 characterized lipids, including phosphatidylcholine (PC), lysophosphatidylcholine (LPC), phosphatidylethanolamine (PE), lysophosphatidylethanolamine (LPE), sphingomyelin (SM), phosphatidylinositol (PI), lysophosphatidylinositol (LPI), phosphatidylserine (PS), phosphoglycerols (PG), and ceramide (Cer), were compared among groups of LPS and LPS+HSW. 14 out 26 LPC, 22 out of 47 PC, 19 out of 29 LPE, 16 out of 36 PE, and 10 out of 15 PI species increased in HSW-treated rat liver, which indicated that HSW may cause liver damage via interfering the phospholipid metabolism. The present work may assist lipid biomarker development of HSW-induced DILI and it also provide new insights into the relationships between phospholipid perturbation and herbal-induced idiosyncratic DILI.